Memory and Society: poetic science and humanistic reference (Psicologia USP, 2008)
The article presents a set of reflections about the book Memória e Sociedade: Lembranças de Velhos, by Eclea Bosi, a masterpiece of Social Psychology and Human Sciences. It tries to point out the original theoretic and methodological approach by bringing out poetry into the scientific construction, redefining the relationship between subject and object of knowledge with the original development of the changing condition between them in the research construction. It also shows how Ecléa Bosis study is based on close bonds between the researcher and the interviewed elderly, in a way to build up a destiny community.